Responsiveness of PROMIS(®) Pediatric Measures to Hospitalizations for Sickle Pain and Subsequent Recovery - Dampier, Carlton (Pediatr Blood Cancer, 2016)
BACKGROUND: The Patient-Reported Outcomes Measurement Information System(®) (PROMIS(®)) created pediatric self-report scales measuring a variety of health attributes (domains), but their responsiveness to changes in health status has not yet been determined in children with sickle cell disease (SCD). PROCEDURE: A convenience cohort of symptomatic SCD children, aged 8-17 years, were asked to complete PROMIS pediatric scales at an initial clinic visit, at the end of a subsequent hospitalization for sickle pain, at a subsequent clinic visit or at home 2-3 weeks after hospitalization, and at a clinic visit 1-2 years after their initial assessment. RESULTS: A total of 121 participants (mean age 12.5 ± 3.1 years, 56.2% female) participated in the study. Pain interference and fatigue domain scores were elevated at baseline, increased substantially during hospitalization, and largely returned to baseline by the recovery period, while the depressive symptoms, anger, and anxiety domain scores displayed a less pronounced elevation during hospitalizations and a slower return to baseline levels. The two physical functioning scales showed a substantial decline in response to hospitalization, but only modest improvements at the recovery assessment, likely representing incomplete recovery. CONCLUSIONS: Several PROMIS Pediatric measures were responsive to changes in health status associated with occurrence and resolution of acute vaso-occlusive pain requiring hospitalization. The substantial differences in these domains during SCD-related pain exacerbations support their potential usefulness in clinical research or in clinical practice. Further studies to characterize variations in symptom patterns over time may provide insights into strategies for more effective management of sickle pain.